Blocking XIAP:CASP7-p19 selectively induces apoptosis of CASP3/DR malignancies by a novel reversible small molecule - Shih-Hsun Chen; Szu-Ying Wu; Yun-Xun Chang; En-Ning Lui; Chih-Kang Chang; Sheng-Wei Lin; Michael Hsiao; Jinn-Moon Yang; Po-Huang Liang (Cell Death and Disease)
Abstract X-linked inhibitor of apoptosis (XIAP) inhibits caspases 3, 7, and 9, thereby preventing cell apoptosis. Endogenous Second mitochondria-derived activator of caspase (Smac) competes out the binding of caspases with XIAP and causes apoptosis, so that Smac mimetics are under clinical trials for anti-cancer chemotherapy. We demonstrated by selectively alkylating caspase 7 (CASP7) to release the active CASP7 for killing the drug-resistant cancer cells with accumulated XIAP:CASP7 resulted from caspase-3 down-regulation (CASP3/DR). However, finding a reversible inhibitor of the protein-protein interaction (PPI) poses a significant challenge. Here, we identified a reversible XIAP:CASP7 inhibitor, 643943, through a multiple-mode virtual screening strategy. In vitro experiments revealed that 643943 bound to CASP7, released the linker-BIR2 domain of XIAP, and activated the caspase. Removing an essential hydroxyl group on 643943 or replacing the OH-interacting Asp93 on CASP7 caused loss of 643943 cytotoxicity, revealing the binding mode. This compound thus selectively killed MCF-7 and other CASP3/DR triple-negative breast cancer cell lines, but not the cancer and normal cell lines expressing higher levels of CASP3 in vitro and in vivo. Moreover, 643943 overcame chemoresistance via down-regulating β-catenin and its associated ABC transporters in paclitaxel-resistant MCF-7 cells. Our studies not only serve as a proof-of-concept for using XIAP:CASP7 as a drug target, but also provide the first reversible XIAP:CASP7 inhibitor for cancer therapy of CASP3/DR malignancies.